A First Step Toward Introducing Emotional Intelligence into the Law School Curriculum: The "Emotional Intelligence and the Clinic Student" Class - Paul J Cain (Legal Education Review)
German legal education and practice in the area of private law is dominated by a specific problem solving methodology. Some German legal writers even suspect that methodology may have taken control over substantive law. Despite its obvious significance, to date such methodology has not provoked much academic discussion. This article introduces the German problem solving model and discusses its significance. It further tries to examine whether other jurisdictions have developed similar methodological tools. In particular, the difference between Civil Law and Common Law seems to suggest that different methodological approaches must be taken in related jurisdictions so far as the handling of private law problems is concerned. Legal education in Common Law systems normally refers to “problem solving” when it comes to ask students to analyse disputes, that is to decide how a specific dispute should be resolved on the basis of the applicable law. As shown below, however, the topic of this article is not limited to merely giving advice on how to deal with problem solving questions in legal examinations in order to guarantee the best possible grades. Further, this article does not aim at the discussion of forms of dispute resolution, such as arbitration, mediation or court proceedings, nor does it address legal writing skills. On the contrary, it focuses on the task of identifying potential (private law) problems arising out of a set of given facts and the sequence in which they should be dealt with. In other words, it discusses the structuring process of private law problem solving, which precedes the actual process of private law problem solving. The methodological devices, which are of relevance in this context, are of direct practical importance for any type of legal work in the area of private law. It is, therefore, the ultimate goal of this article to identify and explain these devices and thus facilitate their application in practice.